Implementor in Advocacy for Mentoring Violence against Women in Pasuruan District - Indra Puspita Sari; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and describe acts of violence against women in Pasuruan Regency as well as analyze and describe the implementers in advocating acts of violence against women in Pasuruan Regency. The research method used is a qualitative approach, data collected through observation, interviews and documentation, while the data sources are primary and secondary data. Informants determined by purposive sampling, the informants include the Head of Gender Mainstreaming Institutionalization (PUG) and Women's Protection, Facilitators and Staff (Data), data analysis derived from Miles and Huberman data, namely through data collection, data, data presentation and conclusion. The results of this study indicate that the implementers in advocating for assistance to acts of violence against women in Pasuruan Regency should be the KBPP Office, and PPT-PPA which consists of various OPD (Regional Apparatus Organizations) as providing support and assistance to victims.